Development and validation of a low-cost simulator for basic CPR skills acquisition - Castagnola, Juan Luis; Freille, Diego German; Barello, Maria del Rosario; Senatore, Paola Beatriz; Vélez Ibarra, María Delfina (Spanish Journal of Medical Education, 2024)
Cardiopulmonary resuscitation, also known as CPR, is a procedure designed to revive people who have stopped breathing or whose heart has stopped beating. The American Society of Cardiology (AHA) recommends using audiovisual feedback devices during CPR for real-time optimization of the effectiveness of the maneuvers. A project led by engineering faculty and students was created due to the high cost and lack of local availability of feedback devices. The objective was to develop an affordable electromechanical simulator, evaluated by experts and end users, to train future doctors and the general public in CPR who need skills for the management of cardiac arrest. After building the initial prototype, supervised testing was performed to ensure its compatibility with the anatomy and strength of an average human thorax. Corrections and adaptations were made until the expected parameters for CPR training were met according to international standards. Then, a randomized study was carried out with health sciences students who had previous experience in CPR. They were divided into two groups and were asked to perform CPR maneuvers for 2 minutes, with assignment of random numbers independent of their participation group. Finally, both groups will randomly perform 2 minutes in a commercial CPR simulator with feedback. These were monitored by a blind observer who does not know which group each student belongs to and will complete a form where the correct placement of the hands, the frequency of the average compressions and their depth were recorded. The analysis of results shows that the group that used the simulator with real-time feedback had a higher percentage of correct CPR maneuvers compared to the control group. This suggests that our prototype met its objectives by allowing faster and more accurate learning of CPR techniques.